2018
DOI: 10.1111/1468-4446.12375
|View full text |Cite
|
Sign up to set email alerts
|

Privileges and penalties in the legal profession: an intersectional analysis of career progression

Abstract: Intersectionality theory is concerned with integrating social characteristics to better understanding complex human relations and inequalities in organizations and societies (McCall ). Recently, intersectionality research has taken a categorical and quantitative turn as scholars critically adopt but retain existing social categories to explain differences in labour market outcomes. A key contention is that social categories carry penalties or privileges and their intersection promotes or hinders the life chanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…Specifically, as Friedman has argued, workforce data on the socio-economic background of professional organizations' staff composition may contribute to theorizing how pay gaps and class ceilings may vary between organizations or sectors, or how the class may intersect with race and gender. This is in line with recent overviews that have emphasized the need to go beyond single-category explanations and better account for intersectionality (Amis et al, 2021;Benschop, 2021;Janssens and Zanoni, 2021;Tomlinson et al, 2018). Disclosing workforce data may also serve a practical goal as it may enhance public awareness about inequalities and, as such, contribute to some form of political and collective pressure through enhancing transparency.…”
Section: Unpacking the Complexities Of Inequality Via Transparencydri...supporting
confidence: 74%
See 1 more Smart Citation
“…Specifically, as Friedman has argued, workforce data on the socio-economic background of professional organizations' staff composition may contribute to theorizing how pay gaps and class ceilings may vary between organizations or sectors, or how the class may intersect with race and gender. This is in line with recent overviews that have emphasized the need to go beyond single-category explanations and better account for intersectionality (Amis et al, 2021;Benschop, 2021;Janssens and Zanoni, 2021;Tomlinson et al, 2018). Disclosing workforce data may also serve a practical goal as it may enhance public awareness about inequalities and, as such, contribute to some form of political and collective pressure through enhancing transparency.…”
Section: Unpacking the Complexities Of Inequality Via Transparencydri...supporting
confidence: 74%
“…dynamics, seeking to restrict access to opportunities to a limited circle of eligible candidates in order to maintain their professional status (Abbott, 1988). Substantial academic research in this field has shown that these closure regimes are gendered and racialized, disadvantaging women, ethnic minorities and individuals from less privileged backgrounds (e.g., Kay and Hagan, 1998;Kornberger, Carter and Ross-Smith, 2010;Tomlinson et al, 2013Tomlinson et al, , 2018Carter, Spence and Muzio, 2015). Research on professions has also revealed that the most powerful professional services firms, deriving from a handful of largely Anglo-Saxon economies, are instrumental in maintaining and extending a capitalist and neo-liberal world order (e.g., Reed, 2018), while also contributing to the reproduction of neo-colonial practices and relationships (e.g., Boussebaa, 2015b;Boussebaa and Faulconbridge, 2019).…”
mentioning
confidence: 99%
“… Results may be less meaningful depending on the group specified to serve as the reference, which could be subjective. If one social position being combined is measured poorly, this method could amplify measurement bias Data reduction methods (latent class analysis, profile analysis) ( Aguirre et al, 2016 ; Goodwin et al, 2018 ; Juan et al, 2016 ; Price et al, 2019 ; Taggart et al, 2019 ; Tomlinson et al, 2019 ; Whaley & Dubose, 2018 ) This approach uses a data reduction method to create an “intersectional” variable, such as latent class analysis, principal components analysis, or profile analysis. In essence, all social factors of interest (i.e., gender, race, housing, etc.)…”
Section: Resultsmentioning
confidence: 99%
“…It means young graduates rely on their seniors for learning those aspects which could boost their career graph. This is the point from where female suffering begins (Tomlinson et al 2019).…”
Section: Discussionmentioning
confidence: 99%